Developments of Electrolyte Systems for Lithium–Sulfur Batteries: A Review - Li, Gaoran; Li, Zhoupeng; Zhang, Bin; Lin, Zhan (Frontiers in Energy Research, 2015)
With a theoretical specific energy five times higher than that of lithium–ion batteries (2,600 vs. ~500 Wh kg−1), lithium–sulfur (Li–S) batteries have been considered as one of the most promising energy storage systems for the electrification of vehicles. However, both the polysulfide shuttle effects of the sulfur cathode and dendrite formation of the lithium anode are still key limitations to practical use of traditional Li–S batteries. In this review, we focus on the recent developments in electrolyte systems. First, we start with a brief discussion on fundamentals of Li–S batteries and key challenges associated with traditional liquid cells. We then introduce the most recent progresses in liquid systems, including ether-based, carbonate-based, and ionic liquid-based electrolytes. And then we move on to the advances in solid systems, including polymer and non-polymer electrolytes. Finally, the opportunities and perspectives for future research in both the liquid and solid Li–S batteries are presented.